High-performance human resource management practices and readiness for change: An integrative model including affective commitment, employees' performance, and the moderating role of hierarchy culture - Ikrema H. A Alqudah; Adolfo Carballo-Penela; Emilio Ruzo-Sanmartín (European Research on Management and Business Economics (ERMBE), 2022)
Nowadays, employees' readiness for change plays a key role to implement many organizational change initiatives. Using a sample of 510 bank employees in Jordan, this study seeks to analyze how high-performance human resource management practices and affective commitment impact employees' readiness for change. We also seek to study the role of readiness for change in improving employee performance. The results obtained through statistical analysis demonstrate a positive association between some high-performance human resource management practices with both affective commitment and readiness for change. Results also show a positive relationship between affective commitment and readiness for change. We have also found that readiness for change is positively related to employees' individual performance. Finally, our findings show that hierarchy culture positively moderates the relation of high-performance human resource management practices with affective commitment.
Keywords: M10; M12; M14; M16; M50; 650; Affective commitment; Employee performance; Hierarchy culture; Human resource management; Organizational change; Readiness for change